[Privacy Issue and Union Contacts] - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Incomplete; Letter from Susan Stuntz, Tobacco Institute (TI), to David Greenberg, Philip Morris Management, following up on meeting about privacy project. Provides list of unions of which TI has contact with the general counsel's office. Iterates that TI expects that most of these offices have dealt with the issue of non-workplace discrimination. Indicates that TI staff will meet with union officials.